Dampak Work life balance dan Lingkungan Kerja terhadap Kinerja Karyawan - Monivca, Olivia Arina; Alvianna, Stella; Hidayatullah, Syarif; Setioko, Danang (Business Management Research, 2024)
Hotel Santika is one of the 4-star hotels in Malang City, and is a favorite hotel in Malang City. Employee performance can be influenced by work life balance and work environment. The data collection technique used a questionnaire given to all employees of the food and beverage department. The analysis technique used in this study was multiple linear regression testing and hypothesis testing. The results of this study are that there is influence between work life balance on employee performance, but the work environment does not have a significant effect on employee performance.  This means that employees who work in the food and beverage department of Hotel Santika Premiere Malang have a balance between work life and personal life